Zur Rolle der Projektion in mathematischer Rede: Ein Beitrag zur Strukturanalyse mathematischer Argumentationen (mathematica didactica, 2014)
New objects of mathematical practices mainly are constituted from existing ones by processes of abstraction and ideation. Corresponding modes of speech, which in the first place allow to speak of and about the new objects, are tacitly presupposed in the course of such processes. As they vastly contribute to the reconstruction of material notions of formal objects the connections of different modes of speech are essential for the analysis of mathematical argumentations. This paper focuses on the role of the projection, leading from formal to material modes of speech.